Differential bioactivity of four BMP-family members as function of biomaterial stiffness. (February 2022) - Sales, Adrià; Khodr, Valia; Machillot, Paul; Chaar, Line; Fourel, Laure; Guevara-Garcia, Amaris; Migliorini, Elisa; Albigès-Rizo, Corinne; Picart, Catherine
Abstract: While a soft film itself is not able to induce cell spreading, BMP-2 presented via such soft film (so called "matrix-bound BMP-2") was previously shown to trigger cell spreading, migration and downstream BMP-2 signaling. Here, we used thin films of controlled stiffness presenting matrix-bound BMPs to study the effect of four BMP members (BMP-2, 4, 7, 9) on cell adhesion and differentiation of skeletal progenitors. We performed automated high-content screening of cellular responses, including cell number, cell spreading area, SMAD phosphorylation and alkaline phosphatase activity. We revealed that the cell response to bBMPs is BMP-type specific, and involved certain BMP receptors and beta chain integrins. In addition, this response is stiffness-dependent for several receptors. The basolateral presentation of the BMPs allowed us to discriminate the specificity of cellular response, especiallyd the role of type I and II BMP receptors and of β integrins in a BMP-type and stiffness-dependent manner. Notably, BMP-2 and BMP-4 were found to have distinct roles, while ALK5, previously known as a TGF-β receptor was revealed to be involved in the BMP-pathway.